Preferensi Profesi Wirausaha Bagi Mahasiswa Fakultas Ekonomi Universitas Islam “45” (Unisma) Bekasi - Isti Pujihastuti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
This research aims to find out the students’ preference of entrepreneurial profession. The sample is the Economics Faculty students at 45 University of Bekasi who have finished the entrepreneurship subject. The research uses questionnaire to gather the information from our sample and conduct a quantitative approach to group the students based on the preferences on entrepreneurial and non-entrepreneurial professions. The researcher conducts the discriminant analysis and divides the variables into four, namely personal character, decision-making, cooperation, and work environment. Descriptively, personal character variable shows the highest value (73,33% from 100%) while work environment variable shows the lowest value (50.88% from 100%). The results are: 1) personal character and cooperative variables are significant in classifying students based on their preferences as entrepreneur or non-entrepreneur; 2) work environment and decision-making variables are not significant.